Excretory urographic, ultrasonographic, and cystoscopic characteristics of urinary bladder abscesses in a dog - Carneiro, Rafael K. [UNESP]; Pereira, Tainara; Brun, Maurício V.; Cruz, Igor C. da [UNESP]; Antunes, Bernardo N.; Pozzobon, Ricardo; Feliciano, Marcus R. (Wiley, 2022)
A 7-year-old male neutered, 6.5 kg, Maltese breed dog was referred with a history of dysuria after undergoing two cystotomies to remove calcium oxalate uroliths. Survey radiographs were inconclusive. Excretory urography allowed visualization of two filling defects in the cranioventral urinary bladder region. Ultrasonography showed urinary bladder sediments, a diffusely thickened wall, and two circumscribed intramural/intraluminal structures with an anechoic interior and a smooth and regular surface. The cystoscopic diagnosis was urinary bladder abscesses and urine cultures were positive for Escherichia coli. Antimicrobial/anti-inflammatory therapy was started with good clinical outcomes and negative culture after 21 days.
Keywords: canine; cyst; cystoscopy; drainage